1997
DOI: 10.1074/jbc.272.52.32988
|View full text |Cite
|
Sign up to set email alerts
|

A 21-kDa C-terminal Fragment of Protein-disulfide Isomerase has Isomerase, Chaperone, and Anti-chaperone Activities

Abstract: A catalyst of disulfide formation and isomerization during protein folding, protein-disulfide isomerase (PDI) has two catalytic sites housed in two domains homologous to thioredoxin, one near the N terminus and the other near the C terminus. The thioredoxin domains, by themselves, can catalyze disulfide formation, but they are unable to catalyze disulfide isomerizations (Darby, N. J. and Creighton, T. E. (1995) Biochemistry 34, 11725-11735). A 21-kDa, C-terminal fragment of PDI (amino acids 308 -491), termed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…3 domain combination with high isomerization activity. At increasing concentrations of reduced RNase, the reaction reaches saturation at 30 M (data not shown), which is similar to the behavior of a 21-kDa C-terminal PDI fragment (25). The reconstructed PDI molecule in which the natural linker between the domains has been replaced by Gly-Ser (abbac) has the same activity as wtPDI.…”
Section: Expression Of Pdi Domains and Multidomain Constructs-supporting
confidence: 59%
See 1 more Smart Citation
“…3 domain combination with high isomerization activity. At increasing concentrations of reduced RNase, the reaction reaches saturation at 30 M (data not shown), which is similar to the behavior of a 21-kDa C-terminal PDI fragment (25). The reconstructed PDI molecule in which the natural linker between the domains has been replaced by Gly-Ser (abbac) has the same activity as wtPDI.…”
Section: Expression Of Pdi Domains and Multidomain Constructs-supporting
confidence: 59%
“…Puig et al reported that "weePDI" (residues 307-491) has 16% of wild-type PDI isomerase activity (25) (Fig. 3).…”
Section: Combinations Of Pdi Domainsmentioning
confidence: 99%
“…The 700-kDa species is presumably a disulfide-bonded high order oligomer. Another C-terminal fragment 308 -491 of PDI has also been reported to behave as a dimer on SEC (39). Therefore, it seemed to us that the species containing the C-terminal 441-491 sequence consistently elutes with an apparent molecular mass equivalent to a dimer on SEC, whereas PDI (1-440) behaves as a monomer.…”
Section: Saxs Parameters-as Shown Inmentioning
confidence: 99%
“…As PDI (19) and PDI (308 -491) (39) have been characterized to be monomeric by analytical ultracentrifugation, and also by SAXS for PDI, the C-terminal 441-491 sequence is likely a contributor to the anomalous behavior of these molecules on SEC.…”
Section: Saxs Parameters-as Shown Inmentioning
confidence: 99%
“…Several properties of mammalian PDI domains have been studied. Recent investigations on recombinant fragments have elucidated domains involved in folding (18,19,34), catalysis (19, 34 -36), chaperone activity (35,37), and peptide/protein recognition (38).…”
mentioning
confidence: 99%